Consumer Protection against Upselling Practices in Food Product Marketing Strategies - Ulya, Selma Lailatul; Latumahina, Rosalinda Elsina (CV. Era Digital Nusantara, 2025)
In the marketing industry, sales strategies are essential to increase the number of product sales. Business actors use various sales strategies to ensure that their goods sell quickly in the market and in demand, making customers tempted. The transaction process that occurs in the relationship between business actors and consumers continues to develop, which has an impact on changes in the legal construction that occurs in the relationship between business actors and consumers. The practice of upselling, which is often used by business actors in the food industry, can potentially harm consumers if it lacks transparency and clear consent. Therefore, efforts to provide protection to consumers are important in this era of free trade. This study aims to assess the extent to which upselling practices comply with existing regulations, as well as provide recommendations to regulators and stakeholders regarding consumer protection and the development of stricter regulations or ethical guidelines. The research method used is normative and legal, using secondary data sources and based on primary law. The findings show that although upselling is allowed, business actors must provide accurate information to consumers. This research concludes that there is a need for stricter law enforcement and increased awareness of businesses and consumers about their rights and obligations to prevent harmful practices.